THE EFFECTIVENESS OF HEALTH EDUCATION VIDEO USING JAMBI'S TRADITIONAL LANGUAGE IN IMPROVING TEETH BRUSHING SKILLS AT ANAK DALAM TRIBE IN PALEMPANG VILLAGE, MUARO JAMBI DISTRICT, JAMBI PROVINCE - Sukarsih Sukarsih; Aida Silfia; Linda Marlia (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2020)
Background: Efforts to improve oral health can be done with preventive and curative measures. Prevention or prevention of dental and oral diseases get top priority. Therefore, it is necessary to develop effective extension media in improving the skills of brushing teeth in the Anak Dalam Tribe in Palempang Village, Muaro Jambi Regency, Jambi Province.The purpose of this study was to determine the effectiveness of the health education video using Jambi's traditional languange in improving toothbrushing skills in the Anak Dalam Tribe in Palempang Village, Muaro Jambi Regency, Jambi Province.. Methods: The design of this study was a Research and Devolution study and data collection from primary data obtained from observation of dental health brushing skills. A sample of 40 people Results: The results of the analysis obtained by the extension of the video in the Jambi-language speaking area was effective in increasing the skills of toothbrushing in children of Suku Anak Dalam in Palempang Village, Muaro Jambi Regency, Jambi Province, indicated by the significance value at 0,000 (p <0.05). It is recommended that dental health personnel carry out promotional and oral health promotion efforts using a Jambi language-language education video for children of Suku Anak Dalam.